2011
DOI: 10.1007/s00128-011-0291-2
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Plant Species for Phytoremediation of Uranium, Thorium, Barium, Nickel, Strontium and Lead Contaminated Soils from a Uranium Mill Tailings Repository in South China

Abstract: The concentrations of uranium, thorium, barium, nickel, strontium and lead in the samples of the tailings and plant species collected from a uranium mill tailings repository in South China were analyzed. Then, the removal capability of a plant for a target element was assessed. It was found that Phragmites australis had the greatest removal capabilities for uranium (820 μg), thorium (103 μg) and lead (1,870 μg). Miscanthus floridulus had the greatest removal capabilities for barium (3,730 μg) and nickel (667 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(38 citation statements)
references
References 14 publications
0
35
2
1
Order By: Relevance
“…Previous studies by (Li et al, 2011) has indicated that the removal efficiency of bean plants was higher when exposed to lower concentrations of uranium compared to higher concentration and the time required to attain the same removal efficiency of uranium was longer. Shahandeh and Hossner (2002) have stated that the uranium uptake by the plant is affected by the pH, iron and manganese oxides and the texture of the soil (Shahandeh and Hossner, 2002).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies by (Li et al, 2011) has indicated that the removal efficiency of bean plants was higher when exposed to lower concentrations of uranium compared to higher concentration and the time required to attain the same removal efficiency of uranium was longer. Shahandeh and Hossner (2002) have stated that the uranium uptake by the plant is affected by the pH, iron and manganese oxides and the texture of the soil (Shahandeh and Hossner, 2002).…”
Section: Discussionmentioning
confidence: 92%
“…A comparison of the previous work on phytoremediation of uranium either in the field or lab conditions showed that vetiver has a moderate phytoremediation effect compared to other plants like Helianthus annuus, Cyperus iria, Parthenocissus quinquefolia, Panicum maximum, Juncellus serotinus, Brassica junceaand Phragmites australis (Li et al, 2011), (Shahandeh and Hossner, 2002), (Roongtanakiat et al, 2010). Similar to our simulation studies in the tanks; in these reports; the analysis were carried out for a maximum period of 90 days, but the work was performed either under laboratory conditions, or samples were taken only once.…”
Section: Discussionmentioning
confidence: 99%
“…Members of family Brassicace, Thlaspi caerulescens and Amaranth retroflexus are found as hyperaccumulators of Co and Sr (McCutcheon and Schnoor 2003). Li et al (2011) performed studies for the analysis of concentrations of U, Th, Ba, Ni, Sr and Pb in plant species collected from uranium mill tailings. The removal capability of a plant for a target element was assessed.…”
Section: Hyperaccmulatorsmentioning
confidence: 99%
“…The content of uranium in the plants was measured in the following procedures. Two grams of the plant sample was taken and was put into the oven to dry at 105°C for 24 h (Li et al 2011). The sample was digested using the method by Hu et al (2012).…”
Section: Sample Treatmentmentioning
confidence: 99%